2006
DOI: 10.1175/jam2323.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Large-Eddy Simulations of Flow in a Steep Alpine Valley. Part II: Flow Structure and Heat Budgets

Abstract: This paper analyzes the three-dimensional flow structure and the heat budget in a typical medium-sized and steep Alpine valley, the Riviera Valley in southern Switzerland. Aircraft measurements from the MAP-Riviera field campaign reveal a very pronounced valley-wind system, including a strong curvature-induced secondary circulation in the southern valley entrance region. Accompanying radio soundings show that the growth of a well-mixed layer is suppressed, even under convective conditions. Our analyses are bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 31 publications
7
82
0
2
Order By: Relevance
“…In particular, Chow et al (2006) clearly demonstrated the need for high-resolution datasets with a proper nesting procedure, in order to achieve agreement between simulations (obtained through the Advanced Regional Prediction System; ARPS) and observations. Furthermore, Weigel et al (2006) confirmed the reduced growth of the well-mixed layer determined by both cold-air advection in the alongvalley direction and subsidence of warm air from aloft. Routinely operated mesoscale models have also been tested for their reliability in reproducing the structure of the convective boundary layer in the context of a valley (Doran et al, 2002;De Wekker et al, 2005;Chow et al, 2006;Weigel et al, 2007b), allowing the identification of the processes which require far greater care when compared to measurements.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, Chow et al (2006) clearly demonstrated the need for high-resolution datasets with a proper nesting procedure, in order to achieve agreement between simulations (obtained through the Advanced Regional Prediction System; ARPS) and observations. Furthermore, Weigel et al (2006) confirmed the reduced growth of the well-mixed layer determined by both cold-air advection in the alongvalley direction and subsidence of warm air from aloft. Routinely operated mesoscale models have also been tested for their reliability in reproducing the structure of the convective boundary layer in the context of a valley (Doran et al, 2002;De Wekker et al, 2005;Chow et al, 2006;Weigel et al, 2007b), allowing the identification of the processes which require far greater care when compared to measurements.…”
Section: Introductionsupporting
confidence: 63%
“…They speculate that the surface heat fluxes, and thus w * , are essential for the heating of the valley atmosphere, either directly by heat flux divergence, or indirectly via thermally driven cross-valley circulations. Indeed, Rampanelli et al (2004) and Weigel et al (2006) showed that overshooting slope winds induce subsidence of potentially warmer air over the valley core. Both studies identified this process as the key driver of valley heating.…”
Section: Introductionmentioning
confidence: 99%
“…In the Riviera Valley, RAMS (Pielke et al, 1992) was successfully used at 330 m resolution (De Wekker et al, 2005) and the Advanced Regional Prediction System LES code (Xue et al, 2000) was used in a horizontal resolution as fine as 150 m Weigel et al, 2006) with excellent results (i.e. very good correspondence to observations).…”
Section: Numerical Modellingmentioning
confidence: 99%
“…This figure is available in colour online at www.interscience.wiley.com/qj 945 improved surface data gives unsatisfactory results. The encouraging conclusion is that simulations using LEStype models can be made so accurately that the model runs may be used to investigate flow characteristics such as driving mechanisms for valley flow or the heat budget in a valley (Weigel, 2005;Weigel et al, 2006).…”
Section: Numerical Modellingmentioning
confidence: 99%
“…These will be performed in the near future and will provide the basis for the comparison with the results reported in the present paper. As a matter of fact, the meteorological fields produced by RK inherently provide a degree of spatial detail that is comparable with the resolution of large-eddy simulations, which are able to resolve explicitly the ABL structures typically associated with thermally driven winds (see examples in Catalano and Cenedese, 2010;Catalano and Moeng, 2010;Chow et al, 2006;Lehner and Whiteman, 2012;Weigel et al, 2006). Numerical sensitivity analyses will be also carried out to investigate the effects of the valley orientation and curvature, of land use inhomogeneities and of local topographic features.…”
Section: Discussionmentioning
confidence: 99%